2010
DOI: 10.1212/wnl.0b013e3181e0f80a
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness analysis in temporal lobe epilepsy

Abstract: We demonstrated with a high degree of confidence that static and dynamic effects of epilepsy impact similarly the neocortex of patients with hippocampal atrophy and patients with normal hippocampal volumes. On the contrary, areas predicting unfavorable postsurgical outcome were distinct, suggesting different configurations of epileptogenic networks in these 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
205
4
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(240 citation statements)
references
References 43 publications
27
205
4
4
Order By: Relevance
“…Previous studies in adults have documented widespread neocortical atrophy in patients with TLE 17, 18. Although, pediatric HS patients here showed a cluster of neocortical atrophy in the ipsi‐lesional temporal pole, it is much less extensive than the gray–white matter boundary blurring or FLAIR hyperintensities.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Previous studies in adults have documented widespread neocortical atrophy in patients with TLE 17, 18. Although, pediatric HS patients here showed a cluster of neocortical atrophy in the ipsi‐lesional temporal pole, it is much less extensive than the gray–white matter boundary blurring or FLAIR hyperintensities.…”
Section: Discussioncontrasting
confidence: 57%
“…This was as expected given that the inclusion criteria for patients involved a radiological diagnosis of HS. The surface‐based approach, to calculate per‐vertex cortical thickness, normalized FLAIR signal intensity and gray–white matter intensity contrast, demonstrated that while pediatric TLE patients did not show the widespread cortical thinning present in adult cohorts,16, 17, 18, 19 they nevertheless had morphological and intensity changes in ipsi‐lesional temporopolar neocortex. Furthermore, temporopolar FLAIR hyperintensities were more marked in patients with a history of febrile convulsions and blurring of the gray–white matter boundary was correlated with earlier onset of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…findings of more widespread alterations in cortical morphology that extend beyond the hippocampus are consistent with TLE's comorbid deficits in executive, intellectual and language functioning (Oyegbile et al, 2004). More recently, using methods that reconstruct the cortical surface to more precisely measure gray matter structure, researchers found up to 30% reductions in cortical thickness bilaterally in multiple frontal, temporal and occipital regions in TLE patients with MTS compared to controls (Lin et al, 2007;Bernhardt et al, 2010;Kemmotsu et al, 2011). These findings are present in TLE patients with and without MTS but have been shown to be stronger in patients with MTS (Labate et al, 2011).…”
Section: Introductionmentioning
confidence: 93%